Current advances in Hodgkin's lymphoma. Issue 1 (1st March 2019) - Vadakara, Joseph; Andrick, Benjamin; Zheng, Lei
Abstract: Hodgkin's lymphoma is a highly treatable malignancy. It has high cure rates yet there are many patients who relapse or are refractory to treatment. Traditionally, treatment has been with conventional chemotherapy; however, the development of brentuximab vedotin and immune checkpoint inhibitors has revolutionized the care of Hodgkin's lymphoma. This is a review of the current advances in the management of Hodgkin's lymphoma and a review of ongoing clinical trials in the field.